"Synthesis-on" and "synthesis-off" modes of carbon arc operation during synthesis of carbon nanotubes. (December 2017) - Yatom, Shurik; Selinsky, Rachel S.; Koel, Bruce E.; Raitses, Yevgeny
Abstract: Arc discharge synthesis of single-walled carbon nanotubes (SWCNTs) remains largely uncontrollable, due to incomplete understanding of the synthetic process itself. We show that synthesis of SWCNTs by a carbon arc may not constitute a single continuous process, but may instead consist of two distinct modes. One of these, a "synthesis-on" mode, produces the majority of the nanomaterials. During the synthesis-on mode, proportionally more carbon nanotubes are collected than in another mode, a "synthesis-off" mode. Both synthesis-on and synthesis-off modes for a typical arc configuration, employing a hollow anode filled with a mixture of powdered metal catalyst and graphite, were characterized by using in situ electrical, imaging, and spectroscopic diagnostics, along with ex situ imaging and spectroscopy. The synthesis-on mode duration is rare compared to the total arc run-time, helping to explain the poor selectivity found in the final collected products, a known inadequacy of arc synthesis. The rarity of the synthesis on mode occurence may be due to the synthesis off mode being more favorable energetically. Graphical abstract: